2008
DOI: 10.1094/php-2008-0118-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Shift in Virulence of Soybean Cyst Nematode is Associated with Use of Resistance from PI 88788

Abstract: The soybean cyst nematode (SCN) is the most economically important pathogen of soybean in the United States. Most of the SCN-resistant cultivars being grown in this region have resistance derived from a single source, Plant Introduction (PI) 88788. A survey conducted in 2005 showed that 83% of the soybean hectarage in Illinois is infested with SCN, with average population densities high enough to cause significant yield suppression (2,700 eggs/100 cm3 soil). Further characterization of these populations showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 6 publications
0
95
0
1
Order By: Relevance
“…Field SCN populations evolve slowly, but are increasingly exhibiting partial virulence on plants expressing PI 88788-derived Rhg1 (23,24). Understanding the molecular mechanisms of Rhg1-mediated SCN resistance may allow quantitative improvements to Rhg1 resistance through allele diversification, the generation of synthetic improved resistance, and/ or transfer of the widely successful Rhg1-mediated resistance mechanism to other crops, such as wheat or potato.…”
Section: Significancementioning
confidence: 99%
“…Field SCN populations evolve slowly, but are increasingly exhibiting partial virulence on plants expressing PI 88788-derived Rhg1 (23,24). Understanding the molecular mechanisms of Rhg1-mediated SCN resistance may allow quantitative improvements to Rhg1 resistance through allele diversification, the generation of synthetic improved resistance, and/ or transfer of the widely successful Rhg1-mediated resistance mechanism to other crops, such as wheat or potato.…”
Section: Significancementioning
confidence: 99%
“…8). Pathogenicity of the nematode is highly variable and a number of pathotypes have been identified based on their ability to reproduce on a set of soybean differentials (Niblack et al 2008;Niblack and Riggs 2004). During the growing season, soybean cyst nematodes reproduce up to four generations in warmer climates and as few as two in cooler climates.…”
Section: Soybean Cystmentioning
confidence: 99%
“…The most effective methods to manage SCN are to use host resistance and to rotate with non-host crops (Niblack and Chen, 2004). As a likely consequence of the abundant use of a single source of resistance, Niblack et al (2008) found that 70% of the SCN-infested soil samples collected in Illinois had populations that could reproduce on PI 88788. Furthermore, resistance has been bred into cultivars; however, PI 88788 is the predominate source of SCN resistance for cultivars available to growers in the northern United States.…”
Section: Impact Of Soybean Cyst Nematode Resistance On Soybean Yieldmentioning
confidence: 99%